Resolving the publication date of J.W. Randall’s Catalogue of Crustacea brought by Thomas Nuttall and J.K. Townsend, from the west coast of North America and the Sandwich Islands, and an updated checklist of the Decapoda described therein (Crustacea: Achelata, Anomura, Astacidea, Brachyura, Caridea, Dendrobranchiata) - Low, Martyn E. Y. (Zootaxa, 2012)
John Witt Randall (b. 1813, d. 1892; Anonymous 1892: 316) published a Catalogue of the Crustacea brought by Thomas Nuttall and J.K. Townsend, from the west coast of North America and the Sandwich Islands … (hereafter the Catalogue), in the first part of the eighth volume of the Journal of the Academy of Natural Sciences of Philadelphia (Randall 1840).